Dinâmica territorial do conhecimento e da inovação: uma análise da Incubadora Tecnológica de São Carlos (SP) - Tessari, Leandro Marcos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This scientific research analyzes the production and transmission of knowledge and innovation at Technology Incubator ParqTec Foundation, from the relationships and synergies built between the various institutional and social segments, consolidating dynamic networks of scientific-technical and informational learning in innovative territory São Carlos (SP). For the implementation of the research: literature survey; field research in the companies located in the Technology Incubator ParqTec Foundation; and, finally, treatment and analysis of information collected were used. The presence of fixed land resources, along with networks of local connections and transterritorial potentiate the production and the improvement of innovation and knowledge. Thus, the city of São Carlos is a innovative territory which, from the last decades of the twentieth century, has expanded its economic production with the installation of new companies from the local university environment and the proliferation of commercial and service activities, redefining the socio-spatial dynamics present in this city, boosting the relationships with other municipalities in the state and the wiyh rest of the country, besides establishing close relations with globalized markets

A presente investigação científica analisa a produção e a transmissão do conhecimento e da inovação na Incubadora Tecnológica da Fundação ParqTec, a partir das relações e sinergias construídas entre os diversos segmentos institucionais e sociais, consolidando redes dinâmicas de aprendizagens técnicocientificas e informacionais no território inovador de São Carlos(SP). Para a execução da pesquisa utilizou-se levantamento bibliográfico, pesquisa de campo junto às empresas instaladas na Incubadora Tecnológica da Fundação ParqTec, e, por fim, tratamento e análise das informações coletadas. A presença dos recursos territoriais fixos e as redes de conexões locais e transterritoriais potencializam a produção e o aprimoramento da inovação e do conhecimento. Assim, a cidade de São Carlos constitui um território inovador que, a partir das últimas décadas do século XX, ampliou sua produção econômica com a instalação de novas empresas, provenientes do ambiente universitário local e pela multiplicação das atividades comerciais e de serviços, redefinindo as dinâmicas socioespaciais presentes nesta cidade, dinamizando as relações com outros municípios do estado e com o restante do país, além de estabelecer estreita relação com os mercados globalizados
Keywords: Economic geography; Distritos industriais; Geografia econômica; Incubadoras de empresas; Planejamento urbano; Inovações tecnologicas; Gestão do conhecimento; São Carlos (SP)